Mathematics Teacher Education in the Andean Region and Paraguay A Comparative Analysis of Issues and Challenges - Baldin, Yuriko Yamamoto; Malaspina, Uldarico (SpringerBriefs in Education, 2018)
*THIS BOOK WILL SOON BE AVAILABLE AS OPEN ACCESS BOOK* This book is an excellent synthesis of the initial and continuing preparation for Mathematics Teaching in Bolivia, Ecuador, Paraguay and Peru, from which comparative analyses can be made that show similarities and differences, and highlight various perspectives. In February 2016, the 5th Capacity and Networking Project (CANP) workshop of the International Commission on Mathematical Instruction (ICMI) was held in Lima, Peru. The coordination of this two-week workshop was undertaken by an international scientific committee (IPC), with equal participation by mathematicians and mathematics educators from the region and from the international ICMI and IMU community. The goal of CANP5 was to improve the quality of mathematics education in the region, which led to the main theme of the scientific program "Initial and Continued Teacher Education". Country Reports on the main theme of teacher education systems for each country in this region were presented and discussed to detect common issues that might be improved through a collaborative network. One of the most important results of this event was the creation of a Mathematics Education Network, namely the Comunidad de Educación Matemática de America del Sur - CEMAS. This book brings to the international Educational Community an important collection of experiences and ideas in the Mathematics Education of four Latin-American countries in the developing Andean region and Paraguay. The dissemination of these results can promote the search for international collaborative actions in a wider scale.